Traditional fishing technology of fishermen community in Papua - Idris, Usman; Frank, Simon Abdi K.; Muttaqin, Muhammad Zaenul; Ilham (ETNOSIA : Jurnal Etnografi Indonesia, 2021)
This paper aims to describe and analyze the types of traditional fishing technology equipment used by the Tobati Enggros fishermen community to manage and utilize coastal resources in Yotefa Bay, Papua. The research approach used descriptive qualitative. Data collection techniques used were observation and interviews. Then the data analysis includes the stage of data reduction, data description, and data interpretation. The results showed that the traditional fishing technology owned by fishermen Tobati Enggros was divided based on the fishing area, namely the fishing area within the bay, mangrove forest, and outside the bay. The traditional technology used is divided by gender and fishing area. There are three types of boats as transportation technology: semang-semang, kole-kole, and jonson boat, and then the fishing tools are kolowai, stabbing tools, molo glass, nets, and fishing rods. The traditional technology fishing equipment owned can be a cultural capital used as a foothold in development. On the other hand, the fishing pattern using traditional environmentally friendly technology with household-scale catches is linked to marine conservation with subsistence utilization of coastal resources.